Enhancing Multicultural Education: Addressing Educational Disparities Through Teacher Training and Inclusivity - Elliyani, Eli; Marini, Arita; Zakiah, Linda (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Purpose: The purpose of this research is to investigate how teacher leadership, through the Teacher Mover program, influences educational outcomes in elementary schools. The study seeks to understand the relationships between teacher leadership, professional development, school culture, emotional intelligence, and student-centered leadership, and how these factors collectively contribute to improved student performance and engagement. Novelty: This study contributes to the existing literature by providing a comprehensive analysis of the Teacher Mover program, a leadership initiative unique to the Indonesian educational context. It offers new insights into how emotional intelligence and professional development mediate the effects of teacher leadership on school culture and student outcomes, which are often underexplored in similar educational leadership studies. Research Methods: This qualitative study used in-depth interviews, participant observations, and document analysis to collect data from Teacher Movers, principals, and teachers at selected elementary schools. The data were analyzed using thematic analysis, with NVivo software used to organize emerging patterns. Results: The findings indicate that teacher leadership significantly improves educational outcomes by fostering a collaborative school culture, enhancing teacher efficacy through professional development, and promoting student-centered approaches. Emotional intelligence was found to be crucial in navigating leadership challenges and fostering positive relationships. Research Contributions: This research offers practical recommendations for educational leaders by highlighting the importance of teacher leadership, professional development, and emotional intelligence in school improvement. It also contributes to the growing body of literature on distributed leadership and its positive impact on educational outcomes.